Efficacy and Tolerability of First Line Arsenic Trioxide in Combination With All-Trans Retinoic Acid in Patients With Acute Promyelocytic Leukemia: Real Life Experience - Autore, Francesco; Chiusolo, Patrizia; Sorà, Federica; Giammarco, Sabrina; Laurenti, Luca; Innocenti, Idanna; Metafuni, Elisabetta; Piccirillo, Nicola; Pagano, Livio; Sica, Simona (Frontiers in Oncology, 2021)
Acute promyelocytic leukemia is a variant of acute myeloid leukemia characterized by t(15;17) and PML/RAR alfa. The discovery of the molecular pathogenesis has led to the first targeted therapy for acute leukemia: all-trans retinoic acid (ATRA). It is usually associated to anthracycline-based chemotherapy obtaining high response rates, but some potential long-term sequelae including therapy-related malignancies are described. The introduction of arsenic trioxide (ATO) tries to obviate such complications and trials pursued a strategy for the incorporation of ATO into initial therapy with an emphasis on minimizing or even abrogating the use of chemotherapy in selected patients. ATRA plus ATO without chemotherapy was the first attempt to treat low and intermediate-risk patients. Our monocentric experience aims to describe a cohort of patients with newly diagnosed APL effectively treated with ATO plus ATRA underlying its efficacy together with the high grade of tolerability of this association. From January 2009 we diagnosed 23 APL patients who were treated with ATO plus ATRA regimen: 14 males and 9 females patients with a median age of 45 years (range 18-72), for the majority intermediate risk (15 patients, 65%). The treatment was well tolerated and all patients obtained molecular remission after a median time of 3 months (range 1-6 months). All patients proceeded to consolidation phase as outpatients, they remained in molecular response at a median time of 44 months (range 15-127) except for 1 patient and all but one patient are alive and in response at a median follow-up of 48 months (range 9-141) and no late effects have been registered so far. ATO plus ATRA regimen shows a series of advantages in comparison to chemotherapy and it also allowed to treat patients in which chemotherapy could not be the first choice because of the age and the physical status or it could even not be applicable. The association of ATO to ATRA is the first experiment of chemo-free regimen to treat acute leukemia and APL has been modified from a highly fatal disease to a highly curable one even without chemotherapy.